2017
DOI: 10.18632/oncotarget.22005
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine strongly enhances the effect of olaparib on radiosensitivity for HPV neg. but not for HPV pos. HNSCC cell lines

Abstract: At present, advanced stage human Papillomavirus (HPV) negative and positive head and neck squamous cell carcinoma (HNSCC) are treated by intense multimodal therapy that includes radiochemotherapy, which are associated with relevant side effects. Patients with HPV positive tumors possess a far better prognosis than those with HPV negative cancers. Therefore, new therapeutic strategies are needed to improve the outcome especially of the latter one as well as quality of life for all HNSCC patients. Here we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…It was previously shown that HPV‐positive cell lines are characterized by an increased radiosensitivity and chemosensitivity, which is considered to result from a defective cell cycle control as well as impaired DSB repair . The latter was recently shown to result from a defect in HR, which is one of the two main DSB repair pathways relevant for mammalian cells …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was previously shown that HPV‐positive cell lines are characterized by an increased radiosensitivity and chemosensitivity, which is considered to result from a defective cell cycle control as well as impaired DSB repair . The latter was recently shown to result from a defect in HR, which is one of the two main DSB repair pathways relevant for mammalian cells …”
Section: Discussionmentioning
confidence: 99%
“…22,23,25 The latter was recently shown to result from a defect in HR, which is one of the two main DSB repair pathways relevant for mammalian cells. [29][30][31] In respect to this pathway, there are two important key players, Fanconi anemia group D2 protein, FANCD2, and the ataxia telangiectasia and Rad3-related protein, ATR, which are both located on chromosome 3. In fact, when expression of these two proteins were determined for 89 HNSCC tumor samples including 36 from HPV-positive tumors via immunohistochemistry, for HPV-positive tumors the expression of ATR was about eight times lower (P < .001) and for FANCD2, about twofold lower when compared to HPV-negative tumors, which may cause the defect in HR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and five HPV pos. HNSCC cell lines, with the second group showing an enhanced cellular radiosensitivity [24], which is attributed to an impaired DSB repair [25,26]. BEZ235 strongly increases the cellular radiosensitivity of all HNSCC cell lines, independently from HPV status.…”
Section: Introductionmentioning
confidence: 99%